Exploring EFL Teachers’ Beliefs and Practices of Oral Corrective Feedback Across Different Grades - Fauziah, Ulfa Dwi; Andriyanti, Erna (ETERNAL (English Teaching Journal), 2026)
Oral corrective feedback is an essential part in learning English as a foreign language. Teachers' beliefs about oral corrective feedback generally underlie their practices, but some studies showed that sometimes there is a mismatch between teachers' beliefs and actual practices. Previous studies also found that students with different grades have different expectations about oral corrective feedback, making it important for teachers to understand it. Based on the previous findings, this study aimed to examine teachers’ beliefs and practices of oral corrective feedback for students across different grades. This study was a qualitative study, with data collection techniques using interviews and observations. The data was analyzed using thematic analysis. The participants in this study were two early secondary school English teachers located in Yogyakarta. The findings showed that teachers have a positive belief in the importance of oral corrective feedback. Teachers' beliefs about the oral corrective feedback timing match their actual practices. However, there was a mismatch between the strategies believed by grade 7 teachers and actual practices. It showed that teachers adjusted their oral corrective feedback strategies to the real conditions. Overall, the teachers’ practices produced positive uptake from students. This finding emphasized the importance of flexibility in the oral corrective feedback application according to the classroom context.